Report of CCQM-K149 nitrogen mass fraction measurements in milk powder - Medvedevskikh, Maria; Krasheninina, Maria; González Cárdenas, Ivonne Alejandra; Erazo, Laura Vanessa Morales; Forigua, Diego Alejandro Ahumada; Rego, Eliane C P do; Wollinger, Wagner; Monteiro, Tânia M; Carvalho, Lucas J de; Garcia, Steve Ali Acco; Chan, Kelly WY; Fung, Wai-hong; et al. (IOP Publishing, 2019)
CCQM key comparison K-149 in the field of nitrogen mass fraction in milk powder has been performed by the Inorganic Analysis Working Group (IAWG) of the Consultative Committee for Amount of Substance (CCQM). The aim of this key comparison CCQM-K149 is to support National Measurement Institutes (NMIs) and Designated Institutes (DIs) to demonstrate the validity of the procedures they employed for determination of nitrogen mass fraction in milk powder. Mass fraction of nitrogen is a very important pointer because the results of these measurements are often used for the determination of protein mass fraction that is an important indicator of the quality of the vast majority of food products and raw materials, in particular dry milk powder. Proteins-enzymes catalyze chemical reactions, protein along with fats and carbohydrates is one of the indicators characterizing the energy value of food, so its definition is mandatory for all food products. The material, milk powder, used for this key comparison has been selected to be representative of the food products. Furthermore, the material shows good properties regarding homogeneity and stability. The results from the key comparison and other experiments indicates that the milk powder studied is suitable for use as a certified reference material. Ural Scientific Research Institute for Metrology (UNIIM) acted as the coordinating laboratory of this comparison. Eight NMIs and two DIs participated in this key comparison. This report contains the results of the key comparison. KEY WORDS FOR SEARCH Nitrogen; mass fraction; milk powder; CCQM; chemistry; BIPM KCDB; CIPM MRA Main text To reach the main text of this paper, click on Final Report . Note that this text is that which appears in Appendix B of the BIPM key comparison database kcdb.bipm.org/ . The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).